Perdebatan Iman Dan Kufurnya Fir’aun Perspektif Mufasir Dan Sufistik - Saepudin, Saepudin; Waliyullah, Muhammad (Al Ashriyyah, 2021)
Pharaoh was a title for the king of ancient Egypt. Many of his stories are mentioned in the Qur'an, he is mentioned as a ruler who has bad attitudes, however, behind that the al-Qur'an explains that when he died, he had the opportunity to make his faith and Islam plausible. Then what is the state of faith that he offered? al-Khazin (2004) stated that the repentance of Pharaoh was not accepted by Allah SWT because at that time there was no more time to repent. In contrast to Dawani (W. 1512 AD), he stated that his repentance was accepted because he made a vow before the spirit reached the throat. If viewed from two conditions about faith, namely there is a pledge and justification in the heart (Ibrahim Mustafa, 1370 H), then Pharaoh has met these criteria. The author tries to analyze these two problems by using the interpretation method tafsir maudhȗ’i''. The faith made at the end of life is the closing of a good life, and the al-Qur'an explains the end of the life of Pharaoh by pledging to believe and surrender to Allah SWT (QS. Yȗnus / 10: 90)